2020
DOI: 10.1186/s12885-020-07488-8
|View full text |Cite
|
Sign up to set email alerts
|

Preoperative circulating tumor cells to predict microvascular invasion and dynamical detection indicate the prognosis of hepatocellular carcinoma

Abstract: Background This study explored the diagnostic power of preoperative circulating tumor cells (CTCs) for the presence of microvascular invasion (MVI) and the relationship between dynamic changes in postoperative CTCs and prognosis. Methods A total of 137 patients were recruited for the study. Preoperative blood samples were collected from all patients to detect CTCs. The time points for blood collection were before the operation, during the operation, and at 1 week, 1 month, 2 months, 3 months, 6 months, and 1… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
21
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(24 citation statements)
references
References 32 publications
(32 reference statements)
2
21
0
Order By: Relevance
“…Ramirez et al showed in their study that CTC was an essential key for the management of the patients with HCC on the waiting list for liver transplantation [ 35 ]. Zhou et al found CTCs can indicate the prognosis of HCC for its efficacy in predicting microvascular invasion [ 36 ]. Our previous study also revealed that CTC-positive patients had a worse prognosis after LT than CTC-negative patients [ 13 ].…”
Section: Discussionmentioning
confidence: 99%
“…Ramirez et al showed in their study that CTC was an essential key for the management of the patients with HCC on the waiting list for liver transplantation [ 35 ]. Zhou et al found CTCs can indicate the prognosis of HCC for its efficacy in predicting microvascular invasion [ 36 ]. Our previous study also revealed that CTC-positive patients had a worse prognosis after LT than CTC-negative patients [ 13 ].…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies ( Lee et al, 2017 ; Yang et al, 2019b ) have reported some progress in predicting MVI based on radiological evidence. Additionally, serum biomarkers such as the neutrophil-to-lymphocyte ratio or circulating tumor cells have demonstrated some promise in this area ( Nitta et al, 2019 ; Zhou et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…showed that CTC count ≥5 per 5 ml has more predictive value than AFP >400 μg/l and tumor diameter >5 cm (72). The authors found that preoperative CTC amount in the peripheral blood of HCC patients closely correlates with microvascular invasion, while surgical removal of the tumor decreases the CTC burden.…”
Section: Phenotyping and Genotyping Of Circulating Tumor Cellsmentioning
confidence: 95%